2019
DOI: 10.1021/jacs.9b08677
|View full text |Cite
|
Sign up to set email alerts
|

Installation of Minimal Tetrazines through Silver-Mediated Liebeskind–Srogl Coupling with Arylboronic Acids

Abstract: Described is a general method for the installation of a minimal 6-methyltetrazin-3-yl group via the first example of a Ag-mediated Liebeskind–Srogl cross-coupling. The attachment of bioorthogonal tetrazines on complex molecules typically relies on linkers that can negatively impact the physiochemical properties of conjugates. Cross-coupling with arylboronic acids and a new reagent, 3-((p-biphenyl-4-ylmethyl)­thio)-6-methyltetrazine (b-Tz), proceeds under mild, PdCl2(dppf)-catalyzed conditions to introduce mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 72 publications
0
67
0
1
Order By: Relevance
“…[28] Our previous approach to studying this drug target was limited by the need for ascaffold with arelatively uncommon boronic acid group, thus restricting the types of drug candidates that could be studied. [21] We hypothesized that ad ivergent approach could be used to tune reaction kinetics and/or inhibitory affinity of an ew class of tetrazine MAGL probes.A ss hown in Scheme 5, probes 10 a-c were designed based on a4 -(arylsulfonamidomethyl)piperidine scaffold bearing an electrophilic hexafluoroisopropyl (HFIP) carbamate warhead. [29] Thus,r eaction of 2 with the (3-methyl-oxetan-3-yl) methyl ester 8 gave 72 %yield of thiomethyltetrazine 9,which served as common intermediate for the synthesis of furyl-substituted 10 a,v inylether-substituted 10 b,a nd monosubstituted tetrazine 10 c.S topped flow kinetics with 5-hydroxyTCO showed that 10 c was 6.5-times more reactive than 10 b,which in turn was 8.6-fold more reactive than 10 a.All of these probes were 3-162 times more reactive than apreviously described MAGL probe based on ad ifferent drug scaffold (12, [21] Figure S4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Our previous approach to studying this drug target was limited by the need for ascaffold with arelatively uncommon boronic acid group, thus restricting the types of drug candidates that could be studied. [21] We hypothesized that ad ivergent approach could be used to tune reaction kinetics and/or inhibitory affinity of an ew class of tetrazine MAGL probes.A ss hown in Scheme 5, probes 10 a-c were designed based on a4 -(arylsulfonamidomethyl)piperidine scaffold bearing an electrophilic hexafluoroisopropyl (HFIP) carbamate warhead. [29] Thus,r eaction of 2 with the (3-methyl-oxetan-3-yl) methyl ester 8 gave 72 %yield of thiomethyltetrazine 9,which served as common intermediate for the synthesis of furyl-substituted 10 a,v inylether-substituted 10 b,a nd monosubstituted tetrazine 10 c.S topped flow kinetics with 5-hydroxyTCO showed that 10 c was 6.5-times more reactive than 10 b,which in turn was 8.6-fold more reactive than 10 a.All of these probes were 3-162 times more reactive than apreviously described MAGL probe based on ad ifferent drug scaffold (12, [21] Figure S4).…”
Section: Methodsmentioning
confidence: 99%
“…[20] Recently, our group described ap rocedure for the conversion of trimethylorthoacetateinto a3-methyl-6-thioalkyltetrazine that can in turn be used for the installation of minimal tetrazines through the silver-mediated Liebeskind-Srogl coupling with arylboronic acids. [21] This method was limited to trimethylorthoacetate and triethylorthobenzoate,and we hoped to develop ag eneral approach for directly converting ester precursors into tetrazines.H owever,t rimethyl-and triethylorthoesters cannot be prepared directly from esters but instead require nitrile precursors and harshly acidic conditions. [22] Thus,o ur previous method did not enable the use of carboxylic acids or esters as precursors to tetrazines.H ere,w e describe ao ne-pot procedure for the conversion of (3-methyloxetan-3-yl)methyl carboxylic esters (1)i nto unsymmetrical 3-thiomethyltetrazines (3)through condensation of oxabicyclo [2.2.2] octyl (OBO) orthoester [23] intermediates with 2 and subsequent oxidation ( Figure 2C).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] However, classical methods for the synthesis of tetrazine-conjugates mainly rely on amide bond formation between a carboxylic acid derived tetrazine precursor and an amine. 9 A major drawback of this method is the presence of a hydrophobic linker, which has a negative effect on the physiochemical properties of the moiety attached to the tetrazine (Scheme 1). 10,11 In this context, the target engagement, metabolism and pharmacological prole of the payloads linked to the tetrazine can be altered drastically.…”
Section: Introductionmentioning
confidence: 99%
“…This divergent approach to synthesizing tetrazine‐coupled probes was applied to the study of MAGL, a serine hydrolase involved in endocannabinoid signaling . Our previous approach to studying this drug target was limited by the need for a scaffold with a relatively uncommon boronic acid group, thus restricting the types of drug candidates that could be studied . We hypothesized that a divergent approach could be used to tune reaction kinetics and/or inhibitory affinity of a new class of tetrazine MAGL probes.…”
Section: Resultsmentioning
confidence: 99%